HyFAT: Affordable hybrid fast address translating device driver for multichannel-based flash devices - Mativenga, Ronnie; Kwon, Se Jin; Chung, Tae Sun (IEEE Transactions on Consumer Electronics, 2019)
Artificial intelligence (AI)-based consumer electronic (CE) devices generate massive amounts of accumulated hot data. Persisting this data into such devices' storage media like the universal flash storage (USF) becomes an issue for flash storage system to manage hot data optimally. Consequently, efforts have been made to support many CE applications and achieve high performance and scalability storage in CE devices. However, it is challenging to find a compatible flash translation layer (FTL) for such flash devices, which can efficiently handle frequent updates imposed by the incoming hot data. Moreover, FTL should be able to handle the hot multimedia data that induces cache-miss penalties which in-turn degrades our flash storage performance. This paper proposes a hybrid flash device for fast address translations called HyFAT which is workload-compatible. HyFAT improves device performance and efficiently manages the combined QuadLevel cell (QLC) for data storage and scalability with SingleLevel cell (SLC) for fast mapping entry storage. The experimental results with realistic workloads show that our approach can improve device performance throughput by 18% on average, compared to traditional DFTL and RFTL.
Keywords: Device Driver; Media; Multichannel; Non-volatile memory; Parallel processing; Performance evaluation; Random access memory; Cache storage; flash memories; multichannel SSD; nonvolatile memory